Chromatin modifiers in endometriosis pathogenesis - K. A. Abaeva; R. T. Murtazova; I. A. Vaniev; A. V. Lazarova; A. A. Sozaeva; M. A. Gogichaeva; A. A. Pirozhnikova; K. V. Ignashev; M. S. Dadashov; D. V. Kolesnikova; A. A. Bayramova; V. E. Kucherskaya; et al. (Акушерство, гинекология и репродукция)
Introduction. It was revealed that various epigenetic abnormalities may play an important role in the endometriosis pathogenesis. The regulation of chromatin structure is carried out mainly by chromatin modifiers (CMs), which stimulate generation of genomic regions with different functional structures and thus change the patterns or levels of gene expression by exerting expected biological functions and causing epigenetic changes.Aim: to consider CMs role in endometriosis pathogenesis and their regulation mechanism assessing current publications.Materials and Methods. The search was conducted in the databases PubMed, Scopus, Web of Science, Google Scholar and eLibrary. Keywords and phrases in Russian and English related to the research topic were used as follows: "endometriosis", "chromatin modifiers", "histone acetylation", "DNA methylation", "microRNA". The evaluation of articles was carried out in accordance with PRISMA recommendations.Results. Chromatin modifiers control differentiation, growth and development, aging and cell death by interacting with various functional chromatin elements. They can cause abnormal gene expression by regulating chromatin structure affecting emergence and development of endometriosis. DNA methylation determines cell types, controls gene expression and genome stability. Abnormal DNA methylation in gene promoter regions necessary for normal endometrial response affects endometriosis development. DNA methyltransferase (DNMT) inhibitors reduce the methylation of human homeobox A10 (HOXA10) and progesterone receptor (PR) genes and potentiate their expression in endometrial cells, improving endometrial susceptibility and inhibiting cell cycle progression. Abnormal histone modifications in endometrial cells may facilitate or hinder the access of transcription mechanisms to chromatin DNA. Histone deacetylase inhibitors effectively eliminate the effects of abnormal histone modifications in endometriosis cells and prevent endometriosis progression. The expression of non-coding RNAs and chromatin remodeling complexes also alters chromatin structure being involved in arising endometriosis and is associated with infertility by promoting proliferation, invasion and migration of endometrioid cells.Conclusion. Chromatin modifiers play a key role in developing endometriosis by controlling gene expression and chromatin structure. Understanding underlying mechanisms provides valuable information for diagnostics and development of new approaches to treat endometriosis.